Factors related to work transition for persons with special needs - Bautista, Maria Yolanda Michelle Agaid (2009)
Persons with special needs (PSNs) face challenges concerning their transition to adulthood. This study identified, described, and analyzed factors related to vocational skills training programs for PSNs. It utilized interviews, surveys, and focus group discussions to gather data regarding perceptions and program participations of PSNs, teachers, parents, management personnel, and consumers. Findings showed that individual skills, interests and motivations for PSNs; attitudes, competencies and program resources for teachers; perceptions, attitudes, and knowledge for management; and product quality and advocacy for consumers helped establish group interconnections and the importance of synergy in transition programs. The research emphasized the crucial role of vocational assessment for PSNs.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: School-to-wotk transition -- Philippines; People with disabilities -- Vocational education -- Philippines